If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6m + 7 + -6m + 12 = 3m + -5m + 5 + -8m + 2 Reorder the terms: 7 + 12 + -6m + -6m = 3m + -5m + 5 + -8m + 2 Combine like terms: 7 + 12 = 19 19 + -6m + -6m = 3m + -5m + 5 + -8m + 2 Combine like terms: -6m + -6m = -12m 19 + -12m = 3m + -5m + 5 + -8m + 2 Reorder the terms: 19 + -12m = 5 + 2 + 3m + -5m + -8m Combine like terms: 5 + 2 = 7 19 + -12m = 7 + 3m + -5m + -8m Combine like terms: 3m + -5m = -2m 19 + -12m = 7 + -2m + -8m Combine like terms: -2m + -8m = -10m 19 + -12m = 7 + -10m Solving 19 + -12m = 7 + -10m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '10m' to each side of the equation. 19 + -12m + 10m = 7 + -10m + 10m Combine like terms: -12m + 10m = -2m 19 + -2m = 7 + -10m + 10m Combine like terms: -10m + 10m = 0 19 + -2m = 7 + 0 19 + -2m = 7 Add '-19' to each side of the equation. 19 + -19 + -2m = 7 + -19 Combine like terms: 19 + -19 = 0 0 + -2m = 7 + -19 -2m = 7 + -19 Combine like terms: 7 + -19 = -12 -2m = -12 Divide each side by '-2'. m = 6 Simplifying m = 6
| 4(3c-1)-5=10c+9 | | .80(x-100)=450 | | -8(t+1)=0 | | 5(x-6)+8=7(x+2)-2 | | 6-2x=5x-9x+9 | | 9y+7=8y-5 | | 2(7+x)=11 | | -12-12-4x=32-28 | | 18x= | | 5(4z-1)-4(z+2)=14(z+1) | | -5z-13z+10=10+7z+3 | | x(3+x)+20=X^2-(x-5) | | 6k-2s=7-2k | | x^2+10x+25-y^2=0 | | 3(d-8)-5=9(d+2)-1 | | A*4-60=A | | 3(5x-4)=8x+12 | | 7+21m=42+14m | | 69+25= | | 69=x-(-5) | | 3.1+7.3= | | 15x+3.5=2 | | 14x+3=7x+9 | | 117=n+40 | | -54=m+(91) | | 8+15p-1=8p+98-6p | | 2y-15+3y=60 | | -89=-80-x | | X^2+36+180=0 | | 15x-5=50 | | -11+x=-11 | | -9x-1.4=5.8 |